Avenida da Boavista. O início e o fim. Praça da República / Foco - Gael Philippe Machado Santos (2012)
Nowadays, there are so many concepts of both city as new parameters to analyze. Watching the city of Oporto, quickly I focused on the centrality of Boavista. This caught my attention immediately for its modern and imposing buildings that are scattered around there. I've lived in the area and crossed every day the roundabout to make way for the Faculty of Architecture and scoured its countless times as long avenue of public transportation till the "Foz"3. As someone who is constantly on the go during the year, I always tried to look with some care and attention to these differences in scale urban design and in particular a very peculiar interest for mega structures. Since I was a child I marvel at the science fiction films and big buildings, with that world futurist and utopian cities as the saga of the "Star Wars" by George Lucas or the classic black and white from 1926, "Metropolis" of Fritz Lange, and his buildings. The big buildings that I see and cross, who clash with a smaller scale, traditional or who engage, I always being fascinated by scale, by is framework or his character "iconic". So, i was thinking that all these buildings deserve particular attention and have important mechanism and roles in the urban design of the city of Porto. This was a great starting point for my work with great potential and for analysis of some spaces of Boa vista Avenue. Venues such that I consider very important as points of intersection and identity of the avenue and the city of Porto to the understanding and analysis of its genesis, characteristics and problems of urban design. Another aspect was the linearity and length of the avenue that led me to think along with the urban diversity of a beginning and an end.